Sonographic evaluation of thyroid nodule based on thyroid imaging reporting and data system classification and its correlation with fine needle aspiration cytology findings - Mandal, Dipta; Mallik, Rikta; Dey, Sayantan; Y. Lama, Kavyanjali (International Journal of Research in Medical Sciences, 2024)
Background: Thyroid nodules, common clinical occurrences, often require diagnostic assessment. Ultrasonography (USG) is primary non-invasive method for detection, with advancing technology enhancing detection capabilities. Fine needle aspiration cytology (FNAC) remains standard but poses risks and expenses. American college of radiology-thyroid image reporting and data system (ACR-TIRADS), introduced in 2017, offers a systematic scoring system based on ultrasound features. This study aims to evaluate USG guided by ACR-TIRADS for accurate nodule classification. Methods: A 1.5-year study at department of radio-diagnosis of BSMCH evaluated thyroid nodules using high-resolution USG based on ACR-TIRADS criteria, followed by FNAC for selected cases, comparing results for concordance. Results: Out of 47 thyroid nodules evaluated, 19.1% were malignant and 80% benign. ACR-TIRADS demonstrated sensitivity, specificity, and accuracy of 66.7%, 87.8%, and 82.9%, respectively. Higher ACR-TIRADS categories correlated with an increased risk of malignancy. Suspicious USG features such as hypo-echogenicity, taller-than-wide shape, lobulated margin, and punctate echogenic foci exhibited significant predictive value for malignancy, with varying levels of sensitivity and specificity. Overall, USG parameters demonstrated notable accuracy in identifying malignant nodules. Conclusions: ACR-TIRADS 2017 reliably predicts thyroid nodule malignancy, reducing unnecessary FNAC procedures, minimizing patient discomfort, and optimizing healthcare resources.